Analysis of the Effect of Service Quality and Customer Satisfaction on the Repurchase Intention, Word of Mouth and Customer Retention for Party Equipment Rental ˋˋSuyono" in Surabaya - Arifin Rahmatulloh, Muchammad Zaenal; Melinda, Tina (KnE Social Sciences, 2021)
The purpose of this study was to provide an understanding of how service quality and customer satisfaction influence the repurchase intention, word of mouth and customer retention at the party equipment rental company “Suyono”in Surabaya. A survey was conducted with 70 service users of “Suyono”. The study used a quantitative approach to explain the causal relationship between the variables. The researcher selected the participants individually. The Partial Least Square analysis technique was used, assisted by the Smart PLS 3.0 application. The results of this study showed that the quality of service had a significant positive effect on customer satisfaction and customer retention; and customer satisfaction had a significant positive effect on repurchase intention and word of mouth. Customer satisfaction did not have a significant effect on customer retention. Therefore, service providers are strongly advised to focus on improving service quality and customer satisfaction to increase customer retention. These results can be applied by companies to increase repurchase intentions, word of mouth and customer retention, especially companies in the service sector. Keywords: service quality, customer satisfaction, repurchase intention, word of mouth